First-principles investigation of gas adsorption on bilayer transition metal dichalcogenides for sensing toxic gases - Jemal Yimer Damte; Hassan Ataalite (Results in Physics)
Transition metal dichalcogenides (TMDs) have shown significant promise in gas sensing applications due to their high catalytic activity and unique electronic properties, which facilitate effective interactions with various gas molecules. This makes them ideal candidates for high-performance gas sensors. In this study, we investigated the sensing properties of nitrogen-containing gases (NCGs) on several heterostructures—namely, MoS2/WTe2, MoTe2/WS2, MoS2/TiO2 and MoS2/IrO2—using density functional theory calculations. The results indicate that NH3 and NOX exhibit weak electronic interactions with MoS2/WTe2 and MoTe2/WS2 heterostructures, while strong electronic interactions are observed with MoS2/TiO2 and MoS2/IrO2 heterostructures. Electron transport properties were further assessed using Non-Equilibrium Green’s Function calculations, revealing promising gas sensing characteristics for NH3 detection across all heterostructures and particularly effective NOX detection with MoS2/WTe2 and MoTe2/WS2 heterostructures. These findings highlight the potential of MoS2/WTe2 and MoTe2/WS2 as sensitive and selective gas sensors for both NH3 and NOX, providing valuable insights for developing advanced gas-sensing technologies with diverse practical applications.